2005
DOI: 10.1038/sj.ejcn.1602340
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet has no effect on markers of inflammation and metabolic risk factors in patients with coronary artery disease

Abstract: Objective: Mediterranean diet is associated with decreased levels of inflammatory markers and metabolic risk factors in epidemiologic studies and recent trials on patients with metabolic syndrome. Given the recent improvements in medical treatments, it is unclear if such beneficial effects are also present in patients with coronary artery disease (CAD). We therefore investigated the effect of Mediterranean diet on markers of inflammation and metabolic risk factors in patients with treated CAD. Design: Randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
2
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(81 citation statements)
references
References 30 publications
1
72
2
6
Order By: Relevance
“…In addition, a significant reduction in CHD mortality has been observed in a secondary prevention trial in patients who followed a Mediterranean-type diet (De Lorgeril et al, 1994). Some (Chrysohoou et al, 2004;Esposito et al, 2004) but not all (Michalsen et al, 2006) studies have suggested that the low cardiovascular risk associated with the Mediterranean-type diet could be mediated in part by inflammation-related factors. Thus, adherence to the Mediterranean diet, was associated with lower concentrations of CRP, IL-6, fibrinogen and white blood cells in a cross-sectional study in Greece (Chrysohoou et al, 2004) and a decrease of inflammatory markers was observed in patients with the metabolic syndrome advised on a Mediterranean-type diet in a 2-year trial (Esposito et al, 2004).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, a significant reduction in CHD mortality has been observed in a secondary prevention trial in patients who followed a Mediterranean-type diet (De Lorgeril et al, 1994). Some (Chrysohoou et al, 2004;Esposito et al, 2004) but not all (Michalsen et al, 2006) studies have suggested that the low cardiovascular risk associated with the Mediterranean-type diet could be mediated in part by inflammation-related factors. Thus, adherence to the Mediterranean diet, was associated with lower concentrations of CRP, IL-6, fibrinogen and white blood cells in a cross-sectional study in Greece (Chrysohoou et al, 2004) and a decrease of inflammatory markers was observed in patients with the metabolic syndrome advised on a Mediterranean-type diet in a 2-year trial (Esposito et al, 2004).…”
Section: Introductionmentioning
confidence: 93%
“…Thus, adherence to the Mediterranean diet, was associated with lower concentrations of CRP, IL-6, fibrinogen and white blood cells in a cross-sectional study in Greece (Chrysohoou et al, 2004) and a decrease of inflammatory markers was observed in patients with the metabolic syndrome advised on a Mediterranean-type diet in a 2-year trial (Esposito et al, 2004). However, no effect of this type of dietary pattern on inflammatory markers was observed in patients with established coronary disease (Michalsen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in a cross-sectional study from the Nurse's Health Study I Cohort, a prudent pattern was associated to low levels of some inflammatory and endothelial function markers in comparison to the results from a Western dietary pattern 69 . Furthermore, the traditional Mediterranean-type diet has been associated to a low risk of cardiovascular disease 106 probably mediated by inflammation related factors 107,108 although some of the results are controversial 109 . Some unpublished results from our group show lower serum concentrations of inflammatory markers, especially those related to endothelial function, in those subjects who consume more fruit, cereals, olive oil and nuts.…”
Section: Healthy Dietary Patternmentioning
confidence: 99%
“…In a randomised controlled study carried out in Naples (Italy) 10 with 180 MS patients, it was observed that in the intervention group (following a Mediterranean-style diet), the prevalence of MS was reduced by 55.6%, as compared with a reduction of 13.3% in the control group (following a prudent diet) in a 2-year period. In another randomised controlled study carried out in Germany 11 with 101 patients with established coronary artery disease, an MD approach could not change metabolic risk factors in a 1-year period. Nevertheless, it must be pointed out that the nutritional intervention developed in the German study was far from being a real MD pattern in some aspects (high intake of red meat and meat products, low use of olive oil, etc.…”
Section: Introductionmentioning
confidence: 99%